'Holy shit, didn't realise my drinking was high risk': an analysis of the way risk is enacted through an online alcohol and drug screening intervention. (1st February 2016) - Savic, Michael; Barker, S. Fiona; Hunter, Barbara; Lubman, Dan I.
Abstract : Commentators view online screening and automated feedback interventions as low-cost ways of addressing alcohol and other drug-related harms. These interventions place people into categories of risk based upon scores from standardised screens and provide automated feedback about a person's level of risk of developing alcohol and other drug 'problems'. In this article, we examine how one particular alcohol and other drug online screening and feedback intervention enacts risky alcohol and other drug use and users, and explore how these enactments compare to alcohol and other drug users' own accounts of risk. In order to do this, we undertook a qualitative analysis of intervention content and intervention recipients' responses ( n  = 489) to an open-ended question about their experience of the online screening and feedback intervention. Our analysis highlights how the online screening and feedback intervention draws on prevention science to cultivate a sense of expertness and objectivity. Intervention recipients' accounts of risk were either overshadowed by the 'expert' risk account provided by the intervention, 'validated' by the intervention or were not accurately reflected by the intervention. In the latter case, intervention recipient comments draw attention to the way in which the intervention enacts alcohol and other drug use as inherently risky without accounting for the context and purpose of use. While the online screening and feedback intervention assumes that people are capable of self-monitoring and managing their alcohol and other drug use and risk, recommendations for help provided enact intervention recipients as fragile and in need of professional help. We suggest that there is a need for the development of interventions that are better equipped to take account of the complexity of alcohol and other drug use and risk experiences and subjectivities.